2020
DOI: 10.3906/tar-1909-67
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic diversity among mutant lemon and mandarin varieties using different molecular markers

Abstract: Mandarin (Citrus reticulate Blanco) and lemon (C.limon L.) are among the most cultivated Citrus species in the world.Among different approaches, gamma radiation is widely used to induce mutations in citrus breeding studies. Gamma radiation causes DNA damage, randomly inducing several mutations in the genome. Molecular techniquesarewidely used to detect such induced mutations and genetic diversity in plants.In this study, simple sequence repeats (SSR), inter-simple sequence repeat (ISSR) and single-strand confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 46 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…ISSR marker clustering analysis is associated with differences in phenotypic traits ( Wu et al., 2020 ), and this identification technique can help distinguish between morphologically distinct plants; it can also provide a solution for early seedling targeted breeding to screen for mutants, as the undirected nature of mutagenesis leads breeders to overlook invisible resistance indicators. Sulu et al. (2020) also used this approach to demonstrate induced mutations and genetic differentiation of citrus and lemon mutant genotypes as an effective tool for determining plant genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…ISSR marker clustering analysis is associated with differences in phenotypic traits ( Wu et al., 2020 ), and this identification technique can help distinguish between morphologically distinct plants; it can also provide a solution for early seedling targeted breeding to screen for mutants, as the undirected nature of mutagenesis leads breeders to overlook invisible resistance indicators. Sulu et al. (2020) also used this approach to demonstrate induced mutations and genetic differentiation of citrus and lemon mutant genotypes as an effective tool for determining plant genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The higher value of I reflects the effectiveness of SSR markers used to identify the variation created by irradiation treatment. Several reports of utilisation of molecular markers for the detection of genetic diversity in mutant population are available in different fruit crops like citrus (Sülü et al, 2020), grapes (Dev et al, 2021), olive (Tekin et al, 2022), and pomegranate (Perveen et al, 2023b). SSR markers have been widely preferred for germplasm characterisation and phylogenetic studies in mango (Azam et al, 2018;Azam et al, 2019;Arogundade et al, 2022).…”
Section: Characterisation Of Putative Mutant Progenies Using Ssr Markersmentioning
confidence: 99%
“…Thusly, in previous studies, differences in cultivars were put forth with principal component analysis in walnuts [42,[59][60][61], kiwifruit [62], strawberry tree [63], hazelnuts [33], almonds [35], raspberry [64], citrus [65] and apricot [66]. All above studies indicated that PCA allows the extraction of the maximum information from used cultivars and underlining the interrelations between variables and individuals, either by similarity or opposition.…”
Section: Eigen Statistics For Two Principal Componentsmentioning
confidence: 99%